2017
DOI: 10.3889/oamjms.2017.198
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pleuran (Β–Glucan from Pleurotus Ostreatus) Supplementation on Incidence and Duration of COPD Exacerbations

Abstract: BACKGROUND:1,3/1,6-β–glucans are recognised as immunomodulators in human and veterinary medicine for over 50 years.AIM:To assess the effects of pleuran (1,3/1,6-β–glucan from Pleurotus ostreatus) on incidence and duration of bacterial exacerbations in patients with COPD.METHODS:We performed an observational, non-randomized, open-label study including 32 COPD patients (Group D) in whom besides the recommended chronic treatment for the stable disease were administered supplement combination containing pleuran 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…In the present study, we found significantly lower incidence of exacerbations, as well as their significantly shorter duration in the study subjects receiving pleuran as compared to their incidence and duration in those who did not receive pleuran. Similar findings were obtained in our study on the effects of pleuran on the incidence and duration of exacerbations in patients with COPD who received the same doses of pleuran over the 3-month period [15]. Similar findings were reported by several studies that investigated effects of pleuran on incidence, duration, and severity of respiratory infections in children [38], [39].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, we found significantly lower incidence of exacerbations, as well as their significantly shorter duration in the study subjects receiving pleuran as compared to their incidence and duration in those who did not receive pleuran. Similar findings were obtained in our study on the effects of pleuran on the incidence and duration of exacerbations in patients with COPD who received the same doses of pleuran over the 3-month period [15]. Similar findings were reported by several studies that investigated effects of pleuran on incidence, duration, and severity of respiratory infections in children [38], [39].…”
Section: Discussionsupporting
confidence: 91%
“…Study subjects from the examined groups had similar demographic characteristics, as well as characteristics related to their disease (mean duration of the disease after diagnosis, severity, etiology, lung function, microbiological findings in the stable phase of the disease, accompanying COPD, etc.). We found a high prevalence of active and passive smokers in both examined groups, which was similar to their prevalence registered in our previous studies [15], [32], [33].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…For instance, cytokines (IL-1 β , IL-6, and TNF- α ), NO synthase, and NF- κ B of the RAW264.7 cells were upregulated upon treatment with Dictyophora indusial polysaccharides [ 14 ]. The β -glucan from Pleurotus Ostreatus , which is another species of mushroom, decreased the incidence and duration of bacterial exacerbations in patients with COPD [ 27 ]. Moreover, Astragalus membranaceus extract reduced the inflammatory response induced by lipopolysaccharide from E .…”
Section: Discussionmentioning
confidence: 99%
“…Studies from various clinical trials and expert opinion reports have shown that the immunosuppressants (IS) are effective in management of COPD in comparison to other conventional treatment [15,16]. IS such as cyclosporine, tacrolimus, CpG (TLR-9 agonists) and few monoclonal antibodies have shown effective results in treating AECB by targeting the prime inflammatory pathways [17,18].…”
Section: Introductionmentioning
confidence: 99%